THE RELEVANCE OF THE MANAGEMENT OF THE PROMOTION ACTIVITIES OF CULTURAL AND LEISURE INSTITUTIONS - J. Akhmedova; Z. Muradova; E. Abakarova (Вестник университета)
In the process of studying the activities of cultural and leisure institutions it has been revealed, that the content of their information and educational activities is closely related to social, psychological and pedagogical processes. It occupies a dominant place in them, as a rule, the content side. The composition of this group includes those forms, in which the content is supplemented by known means of artistic expression. Their common work determines the further specificity of the methodology of information and educational activities of cultural institutions. The increase in the efficiency of existing and the emergence of new cultural and leisure institutions are related directly to advertising.